Peran Guru Pendidikan Agama Kristen sebagai Pembimbing Kerohanian di SDN Cibeureum (Lembaga Pengembangan Kinerja Dosen, 2026)
SDN Cibeureum, the role of Christian religion teachers as spiritual guides is very important in shaping students' character and spiritual development. In addition to acting as educators, these teachers also serve as mentors. They help students recognize themselves as God's creations and instill Christian values such as faith, love, forgiveness, and exemplary behavior. Through consistent spiritual guidance, teachers can provide moral and spiritual support to their students. This helps them face life's challenges and build a positive self-concept. Furthermore, this role includes encouraging and assisting students in developing intellectually, emotionally, socially, and spiritually, so they can grow into responsible and moral individuals. In addition, Christian religion teachers collaborate with families and churches to enhance students' spirituality and character; the Holy Spirit leads them in their work.